Clinical profile in KMT2A-SEPT6-positive acute myeloid leukemia: Does it often co-occur with NRAS mutations? - Chen, Fang; Yang, Ying; Fu, Shuang (Frontiers in Medicine, 2022)
Background The KMT2A-SEPT6 fusion gene is a relatively rare genetic event in leukemia. Its clinical characteristics and prognosis, especially the profile of co-occurring gene mutations remain unclear. Methods We retrospectively analyzed the characteristics of four cases carrying KMT2A-SEPT6 in our hospital, and provided a literature review. Results All the four patients were diagnosed with acute myeloid leukemia (AML) and harbored X chromosome and 11 chromosome rearrangements, they all manifested high levels of D-dimer. Three of four patients had NRAS mutations while one patient with congenital AML did not. Of the four cases, one developed drug resistance, one suffered relapse after bone marrow transplantation (BMT) and two died. Combined with other cases reported in the literature, we found that of all patients diagnosed with AML, 90.9% were children (≤ 9 years old). Patients with white blood cells ≥ 20.0×109/L or diagnosed with M4 had a shorter overall survival (P<0.05). Age, whether to receive BMT, and the chromosome rearrangement patterns had no significant effect on overall survival (P>0.05). Conclusions KMT2A-SEPT6 was more commonly observed in pediatric AML patients, some of which may co-occur with NRAS mutations. The prognosis was related to the white blood cell levels and the leukemia subtype, but was not related to age or BMT. More cases need to be accumulated to better understand the profile in KMT2A-SEPT6-positive AML. KEYWORDS Acute myeloid leukemia; Gene rearrangement; KMT2A-SEPT6; Mutations; NRAS